Politische Reflexion in der Welt des späten Mittelalters: Political thought in the age of scholasticism : essays in honour of Jürgen Miethke - Kaufhold, Martin (Brill, 2010)
This volume investigates the methods of political theory in the later Middle Ages. It presents both, case studies of prominent authors like Marsilius of Padua, William of Ockham or Baldus de Ubaldis, and the attempt to outline the phenomenon of political consultation and its conditions from late antiquity to the Reformation. Questions of specific textual traditions in political commentaries are treated as well as the particular environment in which the authors struggled for influence. The authors of this volume, international specialists in their field and younger historians, came together in Heidelberg on the occasion of J]rgen Miethke4s 65th birthday. The volume also contains J]rgen Miethke4s farewell address to his colleagues, in which he presents some fundamental reflections on the topic of political theory, to which he devoted the bulk of his academic career
Based on a conference held in July 2003 in Heidelberg, Germany. - "Verzeichnis der Schriften von Jürgen Miethke": p. [359]-380. Includes bibliographical references and index. - German or English. - Description based on print version record
"Verzeichnis der Schriften von Jürgen Miethke": p. [359]-380. Includes bibliographical references and index
German or English
Description based on print version record
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002
Keywords: Miethke, Jürgen; Heidelberg <2003>; Electronic books -- Electronic books; Bibliografie; Konferenzschrift -- 2003 -- Heidelberg; Festschrift; Konferenzschrift; Geschichte 1250-1500; Politische Theorie